Evaluating a natural horsemanship program in relation to the ISES first principles of horse training - North, Steve; Hemingway, Ann; McLean, Andrew N.; Laurie, Harriet; Ellis-Hill, Caroline (Elsevier, 2016)
This is the journal version of the abstract previously published in the proceedings of The 12th International Society for Equitation Science Conference (ISES2016)as: Steve North, Ann Hemingway, Andrew N. McLean, Harriet Laurie, and Caroline Ellis-Hill, 2016. Evaluating a natural horsemanship program in relation to the ISES first principles of horse training. In Proceedings of the 12th International Society for Equitation Science Conference (ISES2016) (ifce - institut français du cheval et de l’équitation, Saumur, France, June 23-25 2016), International Society for Equitation Science. http://dx.doi.org/10.5281/zenodo.54733.